Altered expression of Tim family molecules and an imbalanced ratio of Tim-3 to Tim-1 expression in patients with type 1 diabetes - Liu, Yikai; Chen, Zhiying; Xiao, Yang; Chen, Hongzhi; Zhou, Zhiguang (Frontiers in Endocrinology, 2022)
Background: T cell immunoglobulin and mucin domain (Tim) proteins are immunomodulatory molecules that play key roles in the regulation of T cell activation. Published studies have reported that Tim molecules are involved in the pathogenesis of certain autoimmune diseases. Type 1 diabetes (T1D) is an autoimmune disease in which T cells mediate the destruction of islet β cells. However, the expression of Tim molecules in diabetes remains unclear. In this study, we measured the expression of Tim family molecules as well as T cell subset-specific transcription factors in diabetic patients, and we explored the possible involvement of Tim molecules in the pathogenesis of T1D. Method: Forty T1D patients, 36 type 2 diabetes (T2D) patients and 40 healthy controls (HCs) were recruited for this study. Peripheral blood mononuclear cells (PBMCs) were isolated, RNA was extracted from the PBMCs and reverse transcribed into cDNA, and gene expression patterns were analysed by RT–qPCR. Results: Compared with that in HCs, the mRNA expression of Tim-1 and RORC was increased in T1D patients, while the expression of Tim-3 was decreased. The mRNA expression levels of Tim-1 and Tim-4 were increased in T2D patients compared with HCs . In addition, T-bet, GATA3, and RORC expression levels were significantly increased in T2D patients compared to HCs. In addition, compared with HCs, the ratio of Tim-3 to Tim-1 expression in diabetic patients was decreased. The ratios of T-Bet to GATA3 expression and RORC to FOXP3 expression were higher in T1D patients than in HCs. Furthermore, the T1D patients with defective islet function had more significant imbalances in the Tim-3/Tim-1 and RORC/FOXP3 ratios. Moreover, Tim-1 mRNA levels were positively correlated with Tim-4 and RORC mRNA levels in T1D patients Conclusion: Our study revealed altered Tim mRNA expression in the PBMCs of T1D patients. The imbalanced ratios of Tim-3/Tim-1 and RORC/FOXP3 expression were more pronounced in T1D patients with defective islet function. Moreover, Tim-1 mRNA expression was positively correlated with Tim-4 and RORC mRNA expression in T1D patients. All these findings suggest that Tim family molecules may be involved in the pathogenesis of T1D.